A Case Study on Rural Weekly Market at Buyers Doorstep - With Special Reference to "Organic Bhaji" in Kolhapur District of Maharashtra State - Vidya Anandrao Salokhe (New Advances in Business, Management and Economics Vol. 1, 2025)
A market is a place where buyers and sellers come together. A market center performs the exchange of goods and services and also ideas and information. The nature of weekly markets is very old. Weekly markets are held on a specific day of the week. As per the Rural Marketing Association of India, in 2011 Maharashtra had 22300 average numbers of visitors in large weekly markets, while in small weekly markets 10500 customers’ visited approximately in Maharashtra. Nowadays buyers expect door-step services i.e. home delivery, because of their busy lifestyle. The consumers, who are health conscious, prefer organic products i.e. standard and specific choices. This paper attempts to study organic Bhaji, the family venture engaged with providing weekly door-step services.